Tinjauan Teologis Integritas Elia - Rahel Rati Sarungallo; Riana Udurman Sihombing (Jurnal Teologi dan Pelayanan Kerusso, 2019)
Integrity is important as long as someone is still alive. The importance of integrity is so important since the time of Elijah's ministry that was very necessary to bring change in the midst of Israel, which is to return to true worship. The changes brought by Elijah were only determined because Elijah had integrity. How about today, is integrity still relevant for believers? The author himself believes that integrity is still relevant for contemporary believers. The reason, because the success or failure of a person is determined by integrity. Integrity itself has the meaning of the integrity of a person, that means talking about one's own truth.